Efektivitas Manajemen E-System dalam Pelayanan Perpajakan terhadap Kepatuhan Wajib Pajak dalam Pelaporan SPT (E-Filing) - Gunarso, Pujo (Jurnal Manajemen dan Kewirausahaan, 2016)
This purposes of this study is to analyze the influence of management effectiveness ofÂ e-taxation system to tax compliance in terms of reporting such as (e-filing). This research was conducted at the Tax Office Batu region in the tax year 2015. The research method uses a descriptive quantitative method. The results of this study explains that the management of e-filing for the realization of the Key Performance Index e-filing using point based on the rules of the Directorate General of Taxation number: PER-03 / PJ / 2015 has been effective. https://doi.org/10.26905/jmdk.v4i2.656